Exploring the Perceived Integrations Between Assessment and Metacognition: A Qualitative Inquiry of Three Award-Winning Teacher Educators' Conceptions of Assessment in a Hong Kong University Context - Wang, Jing (Frontiers in Education, 2020)
This paper sets out to depict the interactions and integrations between teacher conceptions of assessment and their knowledge of and pedagogical understanding of metacognition. It aims to reframe teacher conceptions of assessment and direct the conceptions to improvement of learning and teaching from a metacognitive perspective, by closely observing the lessons and interviewing three award-winning teacher educators from a Hong Kong university context. The rich qualitative data, deriving from a multiple-case longitudinal design show that the integration was manifested, in different ways, between the conceptions of assessment and knowledge of and pedagogical understanding of metacognition across the three case teachers. Two pertinent issues were discussed concerning perceived dual roles in students in response to both accountability and learning purpose of assessment, and priority of classroom assessment in relation to metacognitive engagement. However exploratory, the perspectives regarding various real classroom decisions and dilemmas, and pedagogical insights that emerged from the specific setting may carry resonance for teachers, researchers and teacher-educators.